EXPLORING ETHNOMATHEMATICS ON THE FISH BREEDING ACTIVITIES IN TAMBAK BULAK, SIDOARJO - Emillia Ardhiana Wulandari; Rini Setianingsih (Program Studi S1 Matematika UNESA, 2022)
Ethnomathematics is a mathematical idea that grows in a culture. Ethnomathematics is an important idea to know the role of mathematics in everyday life. Through ethnomathematics, learning mathematics can be taught in close situations with students. Thus, students will be easier and interested in understanding mathematical concepts at school. Therefore, this study was conducted to identify the ethnomathematical form that exist in fish breeders activities in Tambak Bulak Sidoarjo which focuses on six fundamental activities in a culture. This research is a qualitative research with an ethnographic approach. Data obtained from participant observation and interviews with fish breeders from the Tambak Bulak Sidoarjo community with data collection instruments are observation sheets, interview guidelines, and research note sheets. Furthermore, the data will be analyzed using qualitative data analysis techniques. The results showed that, there were ethnomathematical form in fish breeders activities in Tambak Bulak Sidoarjo related to the concept of numbers, cartesian coordinate system, length, direct proportion, inverse proportion, plane figures namely rectangles, trapezoids, circles, rhombuses, triangles, and pentagons, also the math logic concepts. Thus, fish breeders activities can be used as a bridge to teach mathematical concepts in schools with the hope that students can more easily understand the mathematical concepts. Keyword: ethnomathematics, fish breeding, Tambak Bulak Sidoarjo.